COLDSPOT OF DECELERATED SEA-LEVEL RISE ON THE PACIFIC COAST OF NORTH AMERICA - Parker, Albert (Quaestiones Geographicae, 2016)
We show here the presence of significant “coldspot” of sea level rise along the West Coast of the United States and Canada (including Alaska). The 30-years sea level for the area are mostly falling also at subsiding locations as San Francisco and Seattle where subsidence is responsible for a long term positive rate of rise. The 20 long term tide gauges of the area of length exceeding the 60-years length have a naïve average rate of rise –0.729 mm/year in the update 30-Apr-2015, down from –0.624 mm/year in the update 14-Feb-2014. Therefore, along the West Coast of the United States and Canada the sea levels are on average falling, and becoming more and more negative.